In Vitro Drug Release Studies from a Novel Lyophilised Nasal Dosage Form - Thapa, Panna; Stevens, Howard NE; Baillie, Alan J (Kathmandu University Journal of Science, Engineering and Technology, 2010)
In vitro release of nicotine hydrogen tartrate (NHT) into phosphate buffer saline (PBS), pH 7.4 at 37°C was studied in a diffusion cell, which, with a minimal dissolution volume on the donor side, was intended to mimic the low hydration environment of the nasal mucosa. Lyophilisates prepared from different concentrations (0.25, 0.5, 1, 2 & 3% w/w) of Methocel K4MP solution and K100LVP, K15MP, K100MP solutions (1 & 2%) containing NHT were placed on the diffusion cell membrane which was maintained just in contact with the constantly agitated liquid phase of the receptor compartment. Samples were withdrawn at regular time intervals from the receptor compartment, replaced by fresh medium and analysed spectrophotometrically at 260nm after appropriate dilution. As controls, nicotine release profiles from NHT powder & aqueous solution, Methocel K solutions, and simple powder blends of K4MP were also measured. The nicotine release was dependent on the concentration of Methocel K polymer, whether the donor side of the cell was presented with a solution or lyophilisate of NHT in polymer. Nicotine release decreased with increasing polymer concentration (t50% = 25 min and 75 min for lyophilisate prepared from 1% and 3% w/w K4MP respectively). However at any polymer concentration, nicotine release was faster from solution than from lyophilisate. The difference in nicotine release between solution and lyophilisate became more prominent at higher polymer concentration. Interestingly, nicotine release was independent of Methocel K molecular weight. In vitro nicotine release took place by anomalous diffusion. Keywords: In vitro drug release; lyophilisation; nasal drug delivery; hydroxypropyl methylcellulose (HPMC), nicotine. DOI: 10.3126/kuset.v5i1.2848 Kathmandu University Journal of Science, Engineering and Technology Vol.5, No.1, January 2009, pp 71-86